2013
DOI: 10.2174/1874325001307010428
|View full text |Cite
|
Sign up to set email alerts
|

What is the Experience of Receiving Health Care for Neck Pain?

Abstract: This study used a descriptive phenomenological approach to describe the experience of finding and receiving health services for neck pain. Nineteen participants (18 females, 1 male) with neck pain (>3 months) were interviewed using a semi-structured questionnaire guide. Interviews were recorded, transcribed and coded. Two overarching themes described the experience: complexity in finding effective health care; and the need for informative, personalized, respectful communication. Complexity in finding effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Systematic reviews and recent qualitative work have found that patients with spinal pain appreciate information regarding the cause of their symptoms and ways to manage their condition; further, they are frustrated by the lack of such information in clinical encounters. 19,20 The results of our secondary analyses suggest HEA as an intervention might offer an advantage in meeting these types of informational needs for acute neck pain patients and should be considered more frequently in clinical practice and future research. We also found acute neck pain patients’ global satisfaction to be largely explained by general care and information related factors (e.g., 60% of the variance) but not entirely.…”
Section: Discussionmentioning
confidence: 92%
“…Systematic reviews and recent qualitative work have found that patients with spinal pain appreciate information regarding the cause of their symptoms and ways to manage their condition; further, they are frustrated by the lack of such information in clinical encounters. 19,20 The results of our secondary analyses suggest HEA as an intervention might offer an advantage in meeting these types of informational needs for acute neck pain patients and should be considered more frequently in clinical practice and future research. We also found acute neck pain patients’ global satisfaction to be largely explained by general care and information related factors (e.g., 60% of the variance) but not entirely.…”
Section: Discussionmentioning
confidence: 92%
“…Given that neck pain is common, potentially disabling and costly to society, and that benefit-risk may well vary by condition, high quality studies are still needed to understand the benefits and risks in the neck pain population. Our qualitative research suggests that the side effects associated with medication use can be very concerning for patients and patients may discontinue medications related to these concerns [101]. Specifically patient's worried about how medications would interfere with their ability to participate in normal life roles [101].…”
Section: Discussionmentioning
confidence: 99%
“…Our qualitative research suggests that the side effects associated with medication use can be very concerning for patients and patients may discontinue medications related to these concerns [101]. Specifically patient's worried about how medications would interfere with their ability to participate in normal life roles [101]. Further, patients in our qualitative study indicated that they prefer that physicians present all treatment options and not confine their recommendations to prescriptions of medications alone [101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is critical that KT be pursued, if the potential benefit of new evidence-based interventions is to be manifested as improved clinical outcomes. This is particularly important with respect to neck pain given that suboptimal outcomes have been documented both in terms of quantitative outcomes and qualitative studies that demonstrate patient dissatisfaction with the current delivery of care for their neck pain [75]. …”
Section: Discussionmentioning
confidence: 99%